Concentration‐independent MRI of pH with a dendrimer‐based pH‐responsive nanoprobe. (14th July 2015) - Bhuiyan, Mohammed P. I.; Aryal, Madhava P.; Janic, Branislava; Karki, Kishor; Varma, Nadimpalli R. S.; Ewing, James R.; Arbab, Ali S.; Ali, Meser M.
Abstract : The measurement of extracellular pH (pHe ) has significant clinical value for pathological diagnoses and for monitoring the effects of pH‐altering therapies. One of the major problems of measuring pHe with a relaxation‐based MRI contrast agent is that the longitudinal relaxivity depends on both pH and the concentration of the agent, requiring the use of a second pH‐unresponsive agent to measure the concentration. Here we tested the feasibility of measuring pH with a relaxation‐based dendritic MRI contrast agent in a concentration‐independent manner at clinically relevant field strengths. The transverse and longitudinal relaxation times in solutions of the contrast agent (GdDOTA‐4AmP)44 ‐G5, a G5–PAMAM dendrimer‐based MRI contrast agent in water, were measured at 3 T and 7 T magnetic field strengths as a function of pH. At 3 T, longitudinal relaxivity ( r 1 ) increased from 7.91 to 9.65 mM −1 s −1 (on a per Gd 3+ basis) on changing pH from 8.84 to 6.35. At 7 T, r 1 relaxivity showed pH response, albeit at lower mean values; transverse relaxivity ( r 2 ) remained independent of pH and magnetic field strengths. The longitudinal relaxivity of (GdDOTA‐4AmP)44 ‐G5 exhibited a strong and reversible pH dependence. The ratio of relaxation rates R 2 / R 1 also showed a linear relationship in a pH‐responsive manner, and this pH response was independent of the absolute concentration of (GdDOTA‐4AmP)44 ‐G5 agent. Importantly, the nanoprobe (GdDOTA‐4AmP)44 ‐G5 shows pH response in the range commonly found in the microenvironment of solid tumors. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The ratiometric approach to measure pH does not require knowledge of the concentration of the agent. Dendrimer‐based MRI contrast agent with T 1 and T 2 effects constitutes the only single MRI contrast agent that can accurately measure pHe in a concentration‐independent manner.